Academic language functions and student achievement in biology and algebra - Ramos, Anita C. 1967- (2007)
A recent DepEd implementation of the Integrative-Interactive Approach gave the researcher an idea in testing the relationship between academic language functions and students' achievement in Science and Mathematics. Two academic language tests in Biology and Algebra were designed. The parallel tests were administered within fourteen days or two week's lapse in order to ensure the measurement of the same four skills in these subjects. Results showed that using the four academic functions namely comparison and contrast, classification, description of process, and exemplification in the contents of Science and Math offers potential benefits for improving students' academic achievement.